Immunodiagnostics of Cholera: Current State of the Problem - N. E. Tereshkina; E. A. Mikheeva; Z. L. Devdariani; A. K. Adamov; G. V. Grigoryeva (Проблемы особо опасных инфекций, 2010)
Presented is the survey of the national and foreign literature concerning the questions of improvement of cholera immunodiagnostics. Considered are the problems and prospects of development of different preparations designed for cholera vibrios detection and serologic diagnostics of the disease.